2018
DOI: 10.1161/circulationaha.117.030414
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Biomarkers for Incident Aortic Stenosis Requiring Valvular Replacement

Abstract: We provide evidence that 5 proteins were altered years before AS surgery and that the associations seem to be driven by concurrent atherosclerotic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…These data suggest a nuanced role for IL-17 in arterial wall physiology and atherosclerosis pathophysiology. As already discussed, IL-6 and TGF-␤1 are both elevated in CAVD, but in addition there is an association of IL-17RA concentration in the plasma with worsening disease phenotypes (98). These data taken with the literature on Th17 cells in fibrotic diseases and IL-17 in hypertension and atherosclerosis suggest that they may be involved in CAVD.…”
Section: Cytokines In the T Lymphocyte Maturation Paradigmsupporting
confidence: 63%
“…These data suggest a nuanced role for IL-17 in arterial wall physiology and atherosclerosis pathophysiology. As already discussed, IL-6 and TGF-␤1 are both elevated in CAVD, but in addition there is an association of IL-17RA concentration in the plasma with worsening disease phenotypes (98). These data taken with the literature on Th17 cells in fibrotic diseases and IL-17 in hypertension and atherosclerosis suggest that they may be involved in CAVD.…”
Section: Cytokines In the T Lymphocyte Maturation Paradigmsupporting
confidence: 63%
“…This would also support our original finding of GAL4's association with incident diabetes. 11 Finally, researchers from Sweden, also using the Olink Proseek CVD III panel, 25 reported that GAL4 was associated with aortic stenosis requiring surgery in two separate cohorts and that GAL4 in the discovery cohort was associated with aortic stenosis in the absence of coronary artery disease. The last finding could, however, not be replicated in the validation cohort.…”
Section: Proteins With a Novel Association With Cardiovascular Outcommentioning
confidence: 99%
“…We used a proximity extension assay (PEA), the Olink Proseek® Multiplex Cardiovascular I 96x96 kit (http://www.olink.com/), simultaneously measuring the concentration of 92 cardiovascular candidate proteins. The mentioned proteomics approach has previously been applied to investigate the relationship between novel protein biomarkers and cardiovascular pathologies [18][19][20]. In short, the assay is performed in a 96-well microplate with 92 pairs of oligonucleotidelabeled antibodies and four internal controls.…”
Section: Multiplex Proximity Extension Assaymentioning
confidence: 99%